A comparative analysis of stance features in research article introductions : Malaysian and English authors - Ali Sorayyaei Azar,; Praemela Hassaram,; Farah Imani Mohd Farook,; Nur Hasyimah Romli, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The study of academic writing has gained considerable interest among academia. Good academic writing necessitates the writers’ language talents and their comprehension of accepted rhetorical components. Many researchers have explored non-native authors’ use of metadiscourse markers in academic discourses and how they differ from native speaker authors. However, limited attention has been given to Malaysian authors, precisely stance features in each rhetorical Move of research articles. This study intends to bridge the gap of comparative studies of native and non-native authors in understanding the usages of stance features within the rhetorical moves of research articles, focusing on the “Introduction” section. The present study compared the “Introduction” sections between six British and Australian authors’ research articles and six Malaysian authors’ research articles in applied linguistics. A mixed-method approach was used in this study. The data were firstly analysed qualitatively to identify the rhetorical moves in the “Introduction” section presented in the research article texts using Swales’ (2004) Creating a Research Space (CARS) model. Secondly, the frequency of stance features used in each move was investigated quantitatively using Hyland’s (2005) stance features taxonomy. The findings revealed that the stance features mostly appeared in the first two Moves (Moves 1 & 2) of the “Introduction” section written by Malaysian authors. The most frequently occurred stance features were hedges, followed by boosters, and lastly attitude markers. There were no self-mentions in the non-native speakers’ (NNS) articles. The native speaker (NS) authors, whereas used more stance features in the three moves (Move 1, Move 2, & Move 3) of the “Introduction” section than Malaysian authors. The authorial identity in the NS authors’ articles was strategically constructed by the presence of self-mentions. As such, the results of this study have informed the pedagogical implications, and further research is needed.